Increased Prostaglandin E2 in Brainstem Respiratory Centers Is Associated With Inhibition of Breathing Movements in Fetal Sheep Exposed to Progressive Systemic Inflammation - Stojanovska, Vanesa; Atta, John; Kelly, Sharmony B.; Zahra, Valerie A.; Matthews-Staindl, Eva; Nitsos, Ilias; Moxham, Alison; Pham, Yen; Hooper, Stuart B.; Herlenius, Eric; Galinsky, Robert; Polglase, Graeme R. (Frontiers in Physiology, 2022)
Background: Preterm newborns commonly experience apnoeas after birth and require respiratory stimulants and support. Antenatal inflammation is a common antecedent of preterm birth and inflammatory mediators, particularly prostaglandin E2 (PGE2), are associated with inhibition of vital brainstem respiratory centres. In this study, we tested the hypothesis that exposure to antenatal inflammation inhibits fetal breathing movements (FBMs) and increases inflammation and PGE2 levels in brainstem respiratory centres, cerebrospinal fluid (CSF) and blood plasma. Methods: Chronically instrumented late preterm fetal sheep at 0.85 of gestation were randomly assigned to receive repeated intravenous saline (n=8) or lipopolysaccharide (LPS) infusions (experimental day 1 = 300 ng, day 2 = 600 ng, day 3 = 1200 ng, n=8). Fetal breathing movements were recorded throughout the experimental period. Sheep were euthanised 4 days after starting infusions for assessment of brainstem respiratory centre histology. Results: LPS infusions increased circulating and cerebrospinal fluid PGE2 levels, decreased arterial oxygen saturation, increased the partial pressure of carbon dioxide and lactate concentration, and decreased pH (p<0.05 for all) compared to controls. LPS infusions caused transient reductions in the % of time fetuses spent breathing and the proportion of vigorous fetal breathing movements (P<0.05 vs control). LPS-exposure increased PGE2 expression in the RTN/pFRG (P<0.05 vs. control) but not the pBÖTC (P<0.07 vs. control) of the brainstem. No significant changes in gene expression were observed for PGE2 enzymes or caspase 3. LPS-exposure reduced the numbers of GFAP-immunoreactive astrocytes in the RTN/pFRG, NTS and XII of the brainstem (P<0.05 vs control for all) and increased microglial activation in the RTN/pFRG, preBÖTC, NTS and XII brainstem respiratory centres (P<0.05 vs control for all). Conclusion: Chronic LPS-exposure in late preterm fetal sheep increased PGE2 levels within the brainstem, CSF and plasma, and was associated with inhibition of FBMs, astrocyte loss and microglial activation within the brainstem respiratory centres. Further studies are needed to determine whether the inflammation-induced increase in PGE2 levels plays a key role in depressing respiratory drive in the perinatal period.